Heterogeneous catalytic decarboxylative sulfonylation of cinnamic acids with sodium benzene sulfinates over a manganese(II)-based rod-shaped metal-organic framework catalyst - Ding, Qi-Da; Si, Jin-Ping; Huang, Kun-Lin; Tian, Feng; Chen, Sheng-Chun; Feng, Xue-Jun; He, Ming-Yang; Chen, Qun (Catalysis communications, 2019)
Based on the acid-base mixed-ligand assembly strategy, a stable Mn(II)-based metal-organic framework (denoted as Mn-MOFs), containing 1-D Mn–O–C rod-shaped chains, was hydrothermally synthesized and structurally characterized. This material was demonstrated to be an efficient heterogeneous catalyst for the decarboxylative sulfonylation of cinnamic acids with sodium benzene sulfinates. Moreover, the Mn-MOF catalyst could be recycled up to six times with the retention of both catalytic activity and crystal structure. [Display omitted] •A stable Mn(II) rod-shaped MOF with mixed linkers is hydrothermally synthesized.•Catalytic decarboxylative C–S cross-coupling over the Mn-MOF catalyst is presented.•An efficient production of various vinyl sulfones is demonstrated.